Is There Such a Thing as Religious Belief? - Burley, Mikel (Implicit Religion, 2023)
Whether there is such a thing as religious belief has been queried by philosophers who think the attitudes that get called religious beliefs are radically different from standard types of belief. It is sometimes claimed that so-called religious beliefs are, for example, resistant to experiential evidence in ways that genuine types of belief are not. A recent proponent of this contention, Brian Clack (2016), has argued that the lack of connection between religious attitudes and the world of everyday experience entails that these attitudes should be classified as “belief-like imaginings” rather than as bona fide beliefs. While admitting that contentions such as this prompt useful reflection upon the specificities of religious belief, I argue that the view that what are ordinarily called religious beliefs are not really beliefs amounts to an unwarranted linguistic stipulation. The concept of belief has a diversity of applications rather than being restricted to the narrow subset which dubious empiricist assumptions might lead us to privilege.